The ruddy duck Oxyura jamaicensis in Europe: natural colonization or human introduction? - Muñoz-Fuentes, Violeta; Green, Andy J.; Sorenson, Michael D.; Negro, Juan J.; Vilà, Carles (Molecular Ecology, 2006)
Native to North America, ruddy ducks Oxyura jamaicensis now occur in 21 countries in the western Palaearctic (including Iceland) and their expanding population threatens the native white-headed duck, Oxyura leucocephala , through hybridization and possibly competition for food and nest sites. We used mitochondrial DNA sequences and nuclear microsatellites to test whether the European ruddy duck population is descended solely from the captive population in the UK, which traces to seven individuals imported from the USA in 1948, or, alternatively, has been augmented by natural dispersal of birds from North America. Limited genetic diversity in the European population is consistent with a founder population as small as seven birds. In addition, shifts in allele frequencies at several loci, presumably due to genetic drift in the founding population, result in significant differentiation between the European and North American populations. Despite the recent separation of these populations, almost all individuals could be unambiguously assigned based on their composite genotypes, to one of two distinct populations, one comprising all of the European ruddy ducks we sampled (including those from Iceland and captive birds in the UK) and the other comprising all North American samples. Our results confirm that the European ruddy duck population is likely to derive solely from the captive population in the UK and we find no evidence of recent arrivals from North America or of admixture between ruddy ducks from Europe and North America. Peer reviewed